HIGH PROGNOSTIC IMPACT OF DIALYSIS ADHERENCE AND CARDIOVASCULAR FACTORS ON SURVIVAL IN HEMODIALYSIS PATIENTS (Global Conference on Medical and Health Sciences, 2026)
During follow-up of patients receiving maintenance hemodialysis, it was observed that not all studied parameters were available for every patient, which necessitated an individual-factor analytical approach. Receiver operating characteristic (ROC) analysis was therefore applied to assess the prognostic value of demographic, clinical, and dialysis-related factors influencing patient survival [1,5]. ROC curves of individual predictors are presented in Figure 1.The analysis demonstrated that missed dialysis sessions, chronic heart failure, and the use of a central venous catheter were the strongest negative predictors of survival, whereas several metabolic and demographic factors showed moderate prognostic performance. Dialysis duration, in contrast, acted as a protective factor. Similar findings have been reported in previous observational and registry-based studies [3,9,11].
Keywords: Hemodialysis; survival; ROC analysis; dialysis adherence; vascular access; chronic heart failure; prognosis.